Exploring Japan's Ainu policy in the light of human rights law: a reply to the commentary on my papers from Dr. Naohiro Nakamura - Maruyama, Hiroshi (Polar Record, 2013)
ABSTRACT In order to explore further Japan's Ainu policy, this reply firstly outlines the differences in opinions that between Dr. Nakamura and myself, and secondly addresses some of the main points of my paper published in this journal. Dr. Nakamura takes into consideration domestic circumstances instead of international human rights law, while I emphasise that Japan's international obligations lies in its adherence to international human rights law and that domestic law must conform to international obligations for the Ainu. My paper chronologically summarises Japan's post-war Ainu policy and investigates who and what has influenced this policy and the law.